'Acquired idiotism', by Frederik Lange (1883). Issue 4 (December 2022) - Schioldann, Johan
The little-known writing by Frederik Lange translated in this Classic Text belongs to what can be called the prolegomenal history of the construction of the concept of schizophrenia. It describes one effort to capture the convergence of certain words of diverse coinage (dementia praecox, acquired idiocy, hebephrenia, heboidophrenia, etc.) with some newly accepted concepts (e.g. the temporalization of madness and the view that adolescence was an independent period of life), and with some old behaviours (which for centuries had been called madness, the portmanteau soon to be rebaptized as psychosis). This convergence culminated in the work of Kraepelin, who was to call it 'dementia praecox'. Lange's transitional efforts and pangs can be sensed as he struggles to describe a new form of madness that affects young people.